SAT0227 Low Diagnostic Utility Of Candidate Definitions for a Positive MRi of the Spine in Axial Spondyloarthritis. (23rd January 2014) - Weber, U.; Zubler, V.; Zhao, Z.; Lambert, R. G.; Rufibach, K.; Chan, S. M.; Pedersen, S. J.; Ostergaard, M.; Maksymowych, W. P.
Abstract : Background: A recent consensus statement based on a systematic literature review by the Assessment of SpondyloArthritis International Society suggested the presence of ≥3 corner inflammatory lesions (CIL) or of several corner fat lesions (CFL) as candidate definitions for a positive MRI of the spine in axial spondyloarthritis (SpA) [1 ]. Objectives: To determine data-driven cut-off values for spinal CIL and CFL yielding a specificity ≥90% and to evaluate their diagnostic utility in non-radiographic axial SpA (nr-axSpA) and ankylosing spondylitis (AS). Methods: The study sample comprised 2 independent cohorts A/B of 130 consecutive patients with back pain ≤50 years newly referred to 2 university clinics, and 20 healthy controls, in whom MRI scans of the entire spine were available. Patients were classified according to clinical examination and pelvic radiography as having nr-axSpA (n=50), AS (n=33), or non-specific back pain (NSBP; n=47). Spinal MRI were assessed by 4 blinded readers according to the standardized CanDen modules. Readers recorded bone marrow edema and fat infiltration in the central and lateral/posterior compartment of all 23 discovertebral units. We calculated cut-off values for CIL and CFL to obtain ≥90% specificity and the corresponding area under the curve (AUC) with confidence interval (CI). Finally, we tested the diagnostic utility (mean sensitivity/specificity of 4 readers) of cut-off values for spinal MRI as proposed in the literature (≥3 CIL [1] and ≥5 CFL [2]) for nr-axSpA and AS patients in both cohorts. Results: For cohorts A/B, the rounded lesion cut-offs to obtain ≥90% specificity were 3/2 CIL and 7/10 CFL, respectively. The corresponding AUC for CIL were 0.69 (CI 0.49-0.84) and 0.69 (CI 0.47-0.85) in the 2 cohorts, and for CFL 0.60 (CI 0.43-0.75) and 0.71 (CI 0.56-0.82), respectively. The diagnostic utility of the spinal thresholds of ≥3 CIL and of ≥5 CFL was low in both cohorts when comparing nr-ax SpA versus NSBP. Diagnostic utility of 2 candidate definitions of a positive MRI of the spine in cohorts A/B Conclusions: In this controlled study, the definitions of a positive spinal MRI proposed in a recent consensus statement showed low diagnostic utility in nr-axSpA. While a cut-off of ≥2/≥3 CIL for a positive MRI was optimal, the threshold for CFL was as high as 10. References: Hermann KG et al. ARD 2012;71:1278. [2] Bennett A et al. ARD 2010;69:891. Disclosure of Interest: None Declared